Der Biosphärenpark als regionales Leitinstrument. Das Große Walsertal im Spiegel der Nutzer - Coy, Martin (alpine space - man and environment, 2009)
This publication is based on a research project "Zukünftige Entwicklungsstrategien für den Biosphärenpark Großes Walsertal (Future strategies for the development of the biosphere reserve Grosses Walsertal)", a regional economic and perceptional geographic analysis. This project aimed at an application-oriented contribution towards a social-regional concomitant research in protected areas. This approach fosters self-conception of biosphere reserves as "model regions for sustainable development".